2015
DOI: 10.4103/0366-6999.152483
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Glomerular Filtration Rate may be Attributed to the Microcirculation Damage in Renal Artery Stenosis

Abstract: Background:The decrease of glomerular filtration rate has been theoretically supposed to be the result of low perfusion in renal artery stenosis (RAS). But the gap between artery stenosis and the glomerular filtration ability is still unclear.Methods:Patients with selective renal artery angiogram were divided by the degree of renal artery narrowing, level of estimated glomerular filtration rate (eGFR), respectively. The different levels of eGFR, renal microcirculation markers, and RAS severity were compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Both these indexes have been used to evaluate the occurrence and development of renal dysfunction in patients with diabetes. [323435] However, a retrospective analysis of biopsy data has indicated that approximately 8% of Chinese T2DM patients may have co-existing diabetic nephropathy and nondiabetic renal disease. [36] Such comorbidities may affect prognosis and treatment, and the evaluation of CHD and stroke risks.…”
Section: Discussionmentioning
confidence: 99%
“…Both these indexes have been used to evaluate the occurrence and development of renal dysfunction in patients with diabetes. [323435] However, a retrospective analysis of biopsy data has indicated that approximately 8% of Chinese T2DM patients may have co-existing diabetic nephropathy and nondiabetic renal disease. [36] Such comorbidities may affect prognosis and treatment, and the evaluation of CHD and stroke risks.…”
Section: Discussionmentioning
confidence: 99%
“… 23 In our study, the baseline rGFR of the affected kidney was weakly correlated with the stenosis. Dong et al 24 also found that there was no significant correlation between the changes in GFR and the degree of renal artery stenosis. Moreover, many factors affect the changes in GFR (such as hypertension, nephritis or nephropathy, etc.…”
Section: Discussionmentioning
confidence: 95%